Returnees in Andalucía (Spain): an approach to the cases of Belgium and Argentina - Arjona Garrido, Ángeles (2005)
Andalucía has been, traditionally, a starting point for emigration. Nowadays, the phenomenon has reversed and it receives populations from different parts of the world. To the foreign migrants we have to add the people who have returned to Andalucía. Here, we are going to study the return process from Belgium and Argentina. The results of the investigation show that the migrants who were in Belgium have experienced a circular migration with a clear intention of coming back, based, above all, on fulfillment or a failure to fulfill planned objectives. On the other hand, the case of the Latin American return is different. First of all, those who return are mostly the descendants of the emigrants. In second place, the initial migration has a definitive character; thus, there have been contextual factors—economic decline and lack of prospects—that have caused the return. In third place, the social networks have had a very minor role in the return to Andalucía.